2015
DOI: 10.1126/scisignal.aac5418
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-selective proteotoxicity of verteporfin inhibits colon cancer progression independently of YAP1

Abstract: Yes-associated protein 1 (YAP1) is a transcriptional coactivator in the Hippo signaling pathway. Increased YAP1- activity promotes the growth of tumors, including that of colorectal cancer (CRC). Verteporfin, a drug that enhances phototherapy to treat neovascular macular degeneration, is an inhibitor of YAP1. Here, we found that verteporfin inhibited tumor growth independently of its effects on YAP1 or the related protein TAZ in genetic or chemical-induced mouse models of CRC, in patient-derived xenografts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
169
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(189 citation statements)
references
References 47 publications
19
169
1
Order By: Relevance
“…As a result, the dramatic induction of profibrotic gene expression observed upon AAN at this time point cannot solely be attributed to Yap overexpression. Although the efficacy of VP treatment to inhibit fibrosis in our KS mouse model seems to suggest that Yap is a key mediator of kidney fibrosis, recent work revealed that VP inhibited Stat3 activation in colon cancer independently of VP's function as a Yap inhibitor (61). This observation brings to light the possibility that VP also inhibits fibrosis via other mechanisms in addition to its role as an inhibitor of Yap activity.…”
Section: Discussionmentioning
confidence: 72%
“…As a result, the dramatic induction of profibrotic gene expression observed upon AAN at this time point cannot solely be attributed to Yap overexpression. Although the efficacy of VP treatment to inhibit fibrosis in our KS mouse model seems to suggest that Yap is a key mediator of kidney fibrosis, recent work revealed that VP inhibited Stat3 activation in colon cancer independently of VP's function as a Yap inhibitor (61). This observation brings to light the possibility that VP also inhibits fibrosis via other mechanisms in addition to its role as an inhibitor of Yap activity.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, we verified that verteporfin decreased YAP protein expression, GTIIC reporter activity and mRNA expression of downstream genes AREG and CTGF in H1975 cells. Our results suggest that verteporfin has an effect similar to that of YAP siRNA on inhibiting YAP, and less likely through off-target effects [30]. Verteporfin increased sensitivity of H1975 cells to erlotinib and in combination with erlotinib, synergistically reduced migration, invasion and tumor sphere formation abilities in H1975 cells.…”
Section: Discussionmentioning
confidence: 89%
“…We show that verteporfin reduces YAP and TAZ mRNA levels, suggesting that decreased synthesis of YAP and TAZ may at least partially explain our findings. However, because recent reports have suggested that verteporfin may also cause protein aggregation through oxidative crosslinking and enhanced degradation, 38,39 other effects of this drug may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have also suggested, however, that verteporfin may directly enhance the degradation of certain proteins through oxidative crosslinking and oligomerization. 38,39 Thus, verteporfin may reduce Smad2/3 levels via multiple mechanisms, some of which are likely YAP/TAZ dependent, whereas others may be YAP/TAZ independent.…”
Section: Discussionmentioning
confidence: 99%